Association between Weight Gain during Pregnancy and Pregnancy Outcomes after Dietary and Lifestyle Interventions: A Meta-analysis - Ruifrok, A.E.; van Poppel, M.N.M.; van Wely, M.; Rogozińska, E.; Khan, K.S.; de Groot, C.J.M.; Thangaratinam, S.; Mol, B.W. (American Journal of Perinatology, 2014)
Objectives Lifestyle interventions in obese pregnant women reduce adverse maternal outcomes of pregnancy. However, the association between weight change due to interventions and the actual reduction in complications is unknown. The objective of this study was to determine the association between gestational weight gain (GWG) and the rate of pregnancy complications.Study Design The authors included randomized controlled trials (RCTs) assessing the effect of lifestyle interventions during pregnancy on GWG and adverse maternal and fetal outcomes. For each outcome they assessed the association between GWG and the risk of adverse pregnancy outcomes.Results They analyzed data of 23 RCTs (4,990 women). Increased GWG was associated with a nonsignificant increase in the incidence of preeclampsia (PE) (0.2% per gained kg, 95% confidence interval [CI] 0.5 to 0.9%, p > 0.05), gestational diabetes (GDM) (0.3% per gained kg, 95% CI −0.5 to 1.0%, p > 0.05), and induction of labor (IOL) (1.5% per gained kg, 95% CI −0.9 to 3.9%, p > 0.05).Conclusions Reduction in GWG due to lifestyle interventions in pregnancy had statistically nonsignificant effects on lowering the incidence of PE, GDM, and IOL. Possibly, the beneficial effect of lifestyle interventions on pregnancy outcomes is due to an effect independent of the reduction of GWG.
Keywords: gestational weight gain; lifestyle interventions; diet; pregnancy outcomes; meta-analysis